2021
DOI: 10.48550/arxiv.2108.04483
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Joint Association and Resource Allocation for Multi-Hop Integrated Access and Backhaul (IAB) Network

Abstract: Integrated access and backhaul (IAB) network is envisioned as a novel network architecture for increasing the network capacity and coverage. To facilitate the IAB network, the appropriate methods of wireless link association and resource management are required. In this paper, we investigate the joint optimization problem of association and resource allocation in terms of subchannel and power for IAB network. In particular, we handle the association and resource allocation problems for wireless backhaul and ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Their results showed that the proposed scheme performs almost as well as the optimal centralized algorithm. Lim et al [20] investigated the joint optimization problem of channel association and power control for multi-hop IAB-enabled networks. They used decomposition techniques and the Lagrangian duality method to solve the problem and demonstrated that configuring multihop backhauling improves capacity and coverage.…”
Section: Introductionmentioning
confidence: 99%
“…Their results showed that the proposed scheme performs almost as well as the optimal centralized algorithm. Lim et al [20] investigated the joint optimization problem of channel association and power control for multi-hop IAB-enabled networks. They used decomposition techniques and the Lagrangian duality method to solve the problem and demonstrated that configuring multihop backhauling improves capacity and coverage.…”
Section: Introductionmentioning
confidence: 99%